Influence of Nanocomposites of LDPE Doped with Nano-MgO by Different Preparing Methods on Its Dielectric Properties. (9th June 2015) - Zhang, Wenlong; Dai, Yajie; Zhao, Hong; Zhong, Lidong
Abstract : LDPE doped with nano-MgO can effectively suppress the space charge accumulation in the nanocomposite under DC applied field, and this suppression was affected greatly by the prepared nano-MgO particles. In this paper, the influence of nanocomposite of LDPE doped with nano-MgO by using different preparation methods on their space charge, and volume resistivity as well as DC breakdown strength was researched. The results showed that size of nano-MgO prepared by the traditional heating method was about 22.74 nm, while being only about 12.76 nm by the microwave-assisted method. When the nano-MgO content in the composite was 2 wt% by weight, the space charge accumulation in this composite was obviously reduced; meanwhile both the volume resistivity and DC breakdown strength were enhanced. When nano-MgO was prepared by the microwave-assisted method, the electric properties of its LDPE nanocomposite were obviously better than those of nano-MgO prepared by traditional heating method.